Carbon footprint of crop production in Heilongjiang land reclamation area, China - Chu, Tianshu; Yu, Lu; Wang, Derui; Yang, Zengling (International Journal of Agricultural and Biological Engineering, 2022)
In the context of global warming, agriculture, as the second-largest source of greenhouse gas emissions after industry, had attracted widespread attention from all walks of life to reduce agricultural emissions. The carbon footprint of the planting production system of the Heilongjiang Land Reclamation Area (HLRA), an important commodity grain base in China, was evaluated and analyzed in this paper. On this basis, this paper sought feasible strategies to reduce carbon emissions from two aspects: agronomic practices and cropping structure adjustment, which were particularly crucial to promote the low-carbon and sustainable development of agriculture in HLRA. Therefore, using the accounting methods in IPCC and Low Carbon Development and Guidelines for the Preparation of Provincial Greenhouse Gas Inventories compiled by the Chinese government, relevant data were collected from 2000 to 2017 in HLRA and accounted for the carbon emissions of the planting production system in four aspects: carbon emissions from agricultural inputs, N2O emissions from managed soils, CH4 emissions from rice cultivation and straw burning emissions. Then carbon uptake consisted of seeds and straws. Finally, with farmers' incomes were set as the objective function and carbon emissions per unit of gross production value was set as the constraint, this paper simulated and optimized the cropping structure in HLRA. The results showed that there was a “stable-growing-declining” trend in the total carbon emissions and carbon uptake of the planting production system in HLRA, with total carbon emissions of 2.84×1010 kg and total carbon uptake of 7.49×1010 kg in 2017. In the past 18 years, carbon emissions per unit area and carbon emissions per unit of gross production had both shown a decreasing trend. To achieve further efficiency gains and emission reductions in the planting production system, it was recommended that the local governments strengthen the comprehensive use of straw resources, optimize irrigation and fertilization techniques, and adjust the cropping structure, i.e., increase the planting area of maize and soybeans and reduce the planting area of rice, and increase subsidies to protect the economic returns of planters.Keywords: carbon footprint, carbon emissions, carbon uptake, crop planting structure, Heilongjiang Land Reclamation AreaDOI: 10.25165/j.ijabe.20221501.5588Citation: Chu T S, Yu L, Wang D R, Yang Z L. Carbon footprint of crop production in Heilongjiang land reclamation area, China. Int J Agric & Biol Eng, 2022; 15(1): 182–191.